Indonesia's Defense Politics in the Multipolar Era: A Study on the Modernization of the Indonesian Air Force's Defense Equipment (Alutsista) - Muhammad Ridwan Pramudya; Asep Setiawan; Usni Hasanudin (Riviera Publishing, 2026)
The era of multipolarity, characterized by competition among the United States, China, Russia, and the European Union, has intensified global security dynamics. This competition spans military, technological, and energy domains, making the stability of Indonesia’s airspace increasingly critical. In response, Indonesia has modernized its air power as a deterrence strategy to address both conventional and non-conventional threats. This study analyzes how Indonesia’s defense policies in the era of multipolarity shape the modernization of the Indonesian Air Force’s (TNI AU) weapon systems from 2015 to 2025. Using a qualitative approach with a case study design, the research includes document analysis, policy review, and air defense strategic assessment. The findings show that the modernization efforts are a strategic response to multipolar dynamics, particularly the increasing use of air power in the region, tensions in the South China Sea, and emerging threats like cyber intrusions, foreign UAVs, and hybrid warfare. The study reveals that modernization is driven by operational needs, global political dynamics, and Indonesia’s defense industry capacity. Key measures include the procurement of advanced fighter aircraft, the enhancement of radar networks, the integration of command and control systems, and the development of cyber capabilities. In conclusion, the modernization of TNI AU’s weapon systems strengthens deterrence, maintains regional stability, and enhances the ability to respond to multidimensional threats in the era of multipolarity.